2014
DOI: 10.1172/jci73455
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of pancreatic cancer describe gemcitabine delivery and response

Abstract: Background. The therapeutic resistance of pancreatic ductal adenocarcinoma (PDAC) is partly ascribed to ineffective delivery of chemotherapy to cancer cells. We hypothesized that physical properties at vascular, extracellular, and cellular scales influence delivery of and response to gemcitabine-based therapy.Methods. We developed a method to measure mass transport properties during routine contrast-enhanced CT scans of individual human PDAC tumors. Additionally, we evaluated gemcitabine infusion during PDAC r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
159
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 39 publications
(67 reference statements)
6
159
0
1
Order By: Relevance
“…FMX 0!72 tumor exposure parameters were estimated from FMX values derived from MRI using a simple linear piecewise function (33). We made the assumption that the difference in the contribution of local field inhomogeneities to R2 Ã on the different scan days (captured in the difference between R2 Ã 0,post and R2 Ã 0, pre ) is negligible relative to the change in R2 Ã produced by FMX (captured in the difference between R2 Ã post and R2 Ã pre ).…”
Section: Fmx-mri Analysismentioning
confidence: 99%
“…FMX 0!72 tumor exposure parameters were estimated from FMX values derived from MRI using a simple linear piecewise function (33). We made the assumption that the difference in the contribution of local field inhomogeneities to R2 Ã on the different scan days (captured in the difference between R2 Ã 0,post and R2 Ã 0, pre ) is negligible relative to the change in R2 Ã produced by FMX (captured in the difference between R2 Ã post and R2 Ã pre ).…”
Section: Fmx-mri Analysismentioning
confidence: 99%
“…However, the treatments are still largely ineffective (4). The failure is attributable to many factors, including extrinsic (6) or intrinsic (7) resistance to the conventional therapeutic approaches of chemotherapy. The chemotherapeutic agent gemcitabine is usually the recommended first-line drug for patients with PDAC and is given alone or in combination with other agents (8).…”
Section: Introductionmentioning
confidence: 99%
“…Most tumors, however, will develop rapid resistance to these regimens and will continue to progress by unknown mechanisms. 2,3 As a result, both the median survival and annual death rate for patients with PC have remained unchanged over the past 20 years. 4 To this end, an analysis of phase 1 cancer trials, which used agents with demonstrated efficacy in models derived from established commercially available cancer cell lines, revealed an overall objective response rate in only 3.8% of patients.…”
mentioning
confidence: 99%